COMPARISON OF KNOWLEDGE BEFORE AND AFTER COUNSELING ABOUT HANDWASHING DURING THE COVID-19 PANDEMIC IN ELDERLY SOCIAL SERVICES - Yunardi (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2020)
The knowledge referred to in this study is knowledge before and after counseling about hand washing during the COVID-19 pandemic. Prior knowledge of counseling is the things respondents know about hand washing during the COVID-19 pandemic which is assessed based on their ability to answer the questions on the questionnaire correctly before counseling. Based on the results of the pre-test questionnaire with a rating scale if answered Yes-1 and No-0 it is known that the 30 elderly respondents have an average score of knowledge before being given counseling is 2.3667 rounded up to 2.37. This was obtained from the total amount of pre-tevi data divided by 30 respondents. It can be seen that the answers of the elderly are still relatively low because they have not received more information about hand washing during a pandemic (OVID-1D. Based on the post-test questionnaire that has been distributed with a rating scale if the answers are Yes-1 and No-0, it is known that the 30 elderly respondents have an average score of knowledge after being given counseling which is 9.6667 rounded up to 9.67. This was obtained from the total post-test data divided by 30 respondents. It can be seen that Jansia's answers greatly improved after the counseling about hand washing during the COVID-19 pandemic. This increase in value indicates that there is a difference in the average score of knowledge about prior knowledge and knowledge after counseling about hand washing during the COVID-19 pandemic. Based on the SPSS test that has been carried out (P—0.000: &« — 0.05) Ha (alternative hypothesis) is accepted because the p-value is & 0, 005 so that Ho is rejected at the price of the level of significance (aw) - 5Yo so that the alternative hypothesis is accepted. Thus the conclusion in this study was that there were differences in knowledge before and after counseling about hand washing during the COFID12 pandemic at the Pematangsiantar Elderly Social Service.